POLA PENALARAN ILMIAH DAN KEMAMPUAN PENYELESAIAN MASALAH SINTESIS FISIKA - Nurhayati Nurhayati; Lia Yuliati; Nandang Mufti (Graduate School of Universitas Negeri Malang, 2016)
Scientific reasoning pattern and problem solving ability has an important role in learning physics which associate multiple concept. The study was conducted to describe the change in the pattern category reasoning, problem solving ability level synthesis of physics, and investigate the relationship between the pattern of scientific reasoning and problem solving abilities synthesis of physics students. This study uses a mixed method embedded experimental design. The research instrument used is the treatment and measurement instruments. Changes in the student category intuitive reasoning patterns influenced by the knowledge and experience of students in daily life. Student’s Problem solving ability level of synthesis problem at most are novice level. Novice student solve the problem without recognizing the concept and have a tendency to plug and chug limited to the equation they remembered. The pattern of scientific reasoning and problem solving abilities synthesis of physics has a positive relation.Pola penalaran ilmiah dan kemampuan penyelesaian masalah memiliki peranan penting dalam pembelajaran fisika yang mengaitkan lebih dari satu konsep. Penelitian dilakukan untuk mendeskripsikan perubahan kategori pola penalaran, tingkat kemampuan penyelesaian masalah sintesis fisika, dan mengetahui hubungan antara pola penalaran ilmiah dan kemampuan penyelesaian masalah sintesis fisika siswa. Penelitian ini menggunakan embedded mixed method desain experimental model. Instrumen penelitian yang digunakan adalah instrumen perlakuan dan pengukuran. Perubahan kategori pola penalaran intuisi siswa dipengaruhi oleh pengetahuan dan pengalaman siswa di lingkungan. Tingkat kemampuan penyelesaian masalah sintesis fisika siswa paling banyak adalah novice. Siswa novice menyelesaikan masalah tanpa mengenali konsep dan memiliki kecenderungan plug dan chug sebatas persamaan yang mereka ingat. Pola penalaran ilmiah dan kemampuan penyelesaian masalah sintesis fisika memiliki hubungan yang positif.